2013
DOI: 10.1109/jmems.2013.2240259
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Thin-Film AlN-on-Diamond Lateral–Extensional Resonators

Abstract: In this paper, low-impedance lateral–extensional microresonators are fabricated on a stack of aluminum nitride (AlN) directly deposited on a polished ultrananocrystalline diamond (UNCD) film. The large acoustic velocity of UNCD is utilized to extend the frequency of such resonators beyond 1 GHz while the frequency-defining features are not reduced excessively. In order to promote the growth of a <jats:formula formulatype="inline"><jats:tex Notation="TeX">$c$</jats:tex> </jats:formula>-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Thus, to increase the bandwidth of the filter while maintaining the lowest insertion loss possible, it is best to reduce the electrode separation between the input and output electrodes as much as the fabrication technology allows. as shown in [25], increasing mode number generally improves the Il of the Tpos resonator. Hence, monolithic filters were designed in four different order harmonics while keeping the aspect ratio of the device almost constant.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Thus, to increase the bandwidth of the filter while maintaining the lowest insertion loss possible, it is best to reduce the electrode separation between the input and output electrodes as much as the fabrication technology allows. as shown in [25], increasing mode number generally improves the Il of the Tpos resonator. Hence, monolithic filters were designed in four different order harmonics while keeping the aspect ratio of the device almost constant.…”
Section: Resultsmentioning
confidence: 73%
“…We have previously shown that multi-tethering of the Tpos resonators improves the q, Il, and power handling, while reducing the spurious modes, some of which could be very close to the target mode [22], [25], [26]. because the operation concept of the monolithic filters is similar to that of Tpos resonators, the same technique is adopted here.…”
Section: A Design Conceptmentioning
confidence: 99%
See 3 more Smart Citations